Analisis Pengendalian Persediaan Bahan Baku Rotan Pada Mebel Rotan Palunesia Collection Team Kota Palu - Mohammad Rizki; Sulaeman Miru; Hadayani Hadayani (Universitas Tadulako, 2017)
This research was conducted to; (1) Determine the optimal order quantity of raw rattan at Palunesia Collection Team Rattan Furniture 2014, (2) Knowing the amount of safety stock of raw rattan to be available at Palunesia Collection Team Rattan Furniture 2014, (3) Know the reorder point materials rattan conducted by Palunesia Collection Team Rattan Furniture 2014, (4) To Find out the total inventory cost of raw material should be issued by the rattan at Palunesia Collection Team Rattan Furniture 2014. Selection of a study conducted by purposive (deliberately) with the consideration that Rattan Furniture Palunesia Collection Team is one of the rattan furniture industry is still active to this day of 12 rattan furniture industry in Palu, on the other hand Palunesia Rattan Furniture Collection Team simply producing furniture as the main product. This study was conducted from April to May 2015. The data analysis that used in this research included Economiq Order Quantity (EOQ), Safety Stock, Reorder Point, and Total Inventory Cost. The results indicate that the optimal number of reservations of raw materials for fine rattan in 2014 for rattan poles Amounted to 105.61 kg, for Rattan pitrit optimal order quantity Amounted to 127.34 kg and rattan core optimal order quantity Amounted to 52.20 kg. Safety stock should always be available in 2014 for this type Amounted to 26.28 kg polished rattan, Rattan pitrit of 50.49 kg, and the types of rattan core of 12.37 kg. Reorder point to be done in 2014 for the types of rattan poles when the amount of raw materials Amounted to 30.54 kg, rattan pitrit at the time the raw material Amounted to 55.39 kg, and the types of rattan core when the amount of raw materials Amounted to 14, 32 kg. Total inventory costs incurred in 2014 for this kind of rattan poles Rp. 124,003.00, for a type of rattan pitrit Rp. 119,109.95 and for the types of rattan core Rp. 123,207.14.